La crisis de la democracia en México - Mercado Maldonado, Asael; Gallegos Magdaleno, Nicolás (Nómadas. Critical Journal of Social and Juridical Science, 2008)
The article presents a diagnosis of the democratic Mexican process in his theoretical and practical definition after the presidential election of 2006 incorporating analytical elements as; the conceptualization of the democracy, the aptitude of the electoral instances to organize the elections, the process towards the candidates choice election for the next presidential elections and the complication of the political national climate before the fight for the power.